Regulatory Regimes of Islamic Banking in ASEAN Economic Community (AEC): A Uniting Force in the Industry of the Region - Haqqi, Abdurrahman Raden Aji (Advances in Social Sciences Research Journal, 2017)
ASEAN Economic Integration has provided the platform for ASEAN countries to restructure their finance sectors and move forward to better cooperation among economies. In banking, the ASEAN market’s increasingly free flow of products and services will open up growth opportunities in both retail and wholesale. Brunei with its Islamic Banking Order 2008 expected to gain a 55%-60% share of all banking assets in the country; in Indonesia, after a developmental plan namely the Blueprint of Islamic Banking Development, the country’s commitment was followed by the enactment of the National Act No.21/2008, ratified in July 2008, which provides an adequate legal foundation for the development of Islamic banking; while in Malaysia, to further improve the banking legislation of the industry, It has enacted a new comprehensive Act, the Islamic Financial Services Act that has come into effect in June 2013; The Philippines’ central bank, on the other hand, is pushing several important initiatives in legislation, regulation and taxation to promote Islamic banking in the country; while in Singapore Islamic banking institutions are regulated through a number of amendments to existing regulations and several related guidelines; finally, in Thailand today there is only one Islamic bank operating in the country: the state-owned Islamic Bank of Thailand, established in 2002 under its own banking regulation. How does Islamic banking industry participate and contribute in this market? This paper attempts at discussing regulatory regime of Islamic banking in ASEAN country after the implementation of AEC in the end of 2015.